In silico screening of potential bioactive peptides in milkfish (Chanos chanos) muscle proteins - Ang, Nadia Martina B. (College of Home Economics, University of the Philippines Diliman, 2023)
Identification and isolation of bioactive peptides from fish sources is an emerging research area for their potential use as ingredients in functional foods and nutraceuticals. Bioinformatics tools provide a more cost-effective and time saving method for predicting potential bioactivities in proteins and aiding experimental methods by guiding enzyme selection for producing fish protein hydrolysates (FPHs). Thus, this study used the in silico tool BIOPEP-Uniwesytet Warmińsko-Mazurski (BIOPEP-UWM) to evaluate the potential of ten representative milkfish (Chanos chanos) muscle proteins to release bioactive peptides with 12 proteases and two enzyme combinations. Results revealed that milkfish is a potentially rich source of antioxidant and angiotensin-converting-enzyme (ACE) inhibiting peptides. Pepsin, papain, and bromelain were most effective in liberating ACE inhibitors while proteinase K, pepsin, and ficin were most successful in releasing antioxidant peptides. Combinations of gastrointestinal (GI) enzymes were also shown to release large amounts of both ACE inhibitors and antioxidants. Furthermore, using PeptideRanker, 40 novel peptides were identified after proteolysis. Additional bioinformatic tools like AllerTop, PeptideCutter, ToxinPred, AHTPin, and AnOxPePred were also used in the study to characterize selected novel peptides on their allergenicity, resistance to GI digestion, toxicity, and predicted antihypertensive and antioxidant activities. The present work suggests that C. chanos is a good source of ACE inhibiting and antioxidant peptides and that in silico approaches can serve as theoretical basis for future in vitro and in vivo research on bioactive peptides from C. chanos proteins.